Manufacturing method of reinforced separator

By pre-moistening the casting drum with a non-solvent for the polymer resin, the method simplifies and accelerates the production of thin reinforced separators, enhancing mechanical quality and ionic conductivity, addressing the inefficiencies of previous methods.

JP7626847B2Active Publication Date: 2025-02-04AGFA GEVAERT NV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023518980
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-24
Filing Date
2021-09-09
Publication Date
2025-02-04
Estimated Expiration
2041-09-09

AI Technical Summary

Technical Problem

Existing methods for producing thin reinforced separators for alkaline electrolytic cells are complicated, expensive, and inefficient due to the complexity of applying polymer solutions to both sides of a porous support, leading to manufacturing limitations and potential tearing during coagulation.

Method used

A method involving a casting drum pre-moistened with a non-solvent for the polymer resin, allowing complete impregnation of the dope solution into the porous support before coagulation, enabling faster separation from the drum without the need for diameter expansion or additional belts, thus simplifying and speeding up the process.

Benefits of technology

This approach results in a thinner, mechanically robust separator with improved ionic conductivity, reducing manufacturing time and costs while maintaining high-quality adhesion and operational efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626847000001
    Figure 0007626847000001
  • Figure 0007626847000002
    Figure 0007626847000002
  • Figure 0007626847000003
    Figure 0007626847000003
Patent Text Reader

Abstract

A method for making a reinforced separator, comprising the steps of: providing a porous support (6) on a pre-wetted casting drum (23); applying a dope solution (3) containing a polymer resin and hydrophilic inorganic particles to a side of the porous support opposite the side that contacts the pre-wetted casting drum; performing phase inversion (9, 1) of the applied polymer solution to obtain a reinforced separator; and removing the reinforced separator (7) from the casting drum, wherein the casting drum is pre-wetted with a non-solvent for the polymer resin.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a reinforced separator and its use in alkaline water electrolysis. [Background technology]

[0002] Currently, hydrogen is used in several industrial processes, for example as a raw material in the chemical industry and as a reducing agent in the metallurgical industry. Hydrogen is a fundamental component in the production of ammonia and thus fertilizers, as well as in the production of methanol, which is used in the production of many polymers. Another application area is oil refineries, where hydrogen is used to process petroleum intermediates.

[0003] Hydrogen is also seen as a future energy carrier, meaning that it can be stored and delivered in a usable form. Energy is released through an exothermic combustion reaction with oxygen, which produces water. No greenhouse gases, including carbon, are emitted during such a combustion reaction.

[0004] In order to realize a low-carbon society, the importance of renewable energy that utilizes natural energy such as solar and wind power is increasing.

[0005] The amount of electricity generated by wind power generation systems and solar power generation systems is not constant because it is highly dependent on weather conditions, which can lead to an imbalance in electricity supply and demand. In order to store surplus electricity, so-called power-to-gas technology, which uses electricity to produce gas fuels such as hydrogen, has attracted great interest in recent years. As electricity production from renewable energy sources increases, so does the demand for storing and transporting the produced energy.

[0006] Alkaline water electrolysis is an important production process that can convert electricity into hydrogen.

[0007] In alkaline water electrolysis cells, so-called separators or diaphragms are used to separate electrodes of different polarity, to prevent short circuits between these electronic conductors (electrodes) and to prevent gas crossover, thus preventing the recombination of hydrogen (produced at the cathode) and oxygen (produced at the anode). The separator must perform all these functions and also be a high ionic conductor for the transport of hydroxyl ions from the cathode to the anode.

[0008] Separators are generally provided with a porous support which reinforces the separator and facilitates its handling and introduction into the electrolytic cell, as disclosed in US Pat. No. 5,399,323 (Hydrogen Systems).

[0009] A preferred porous support is one made of polypropylene (PP) or polyphenylene sulfide (PPS) because of its high resistance to high temperature and high concentration alkaline solutions.

[0010] US Patent No. 5,399,663 and US Patent No. 5,399,673 (Agfa Gevaert and VITO) disclose a method for making reinforced separators in which a polymer solution, also called a dope solution, is coated on both sides of a porous support. However, this method is not optimal for making thin separators. Applying a polymer solution to both sides of a thin porous support, which is typical for such thin separators, is a tricky operation and can result in rippling of the separator.

[0011] However, thinner separators with thinner porous supports provide higher ionic conductivity and therefore improved electrolysis efficiency.

[0012] In the method of applying a polymer solution to only one side of a porous support, a temporary support is generally used. For example, in the method disclosed in the above-mentioned Patent Document 1, a dope solution is first applied onto a temporary support. Next, the porous support is immersed in the applied polymer solution. After the solidification step, the temporary support is removed from the obtained reinforced separator.

[0013] An alternative to such temporary supports are so-called supporting casting drums. The casting drum supports the porous support on one side, while the other side of the porous support is coated with the polymer solution. After a solidification step, the resulting separator is removed from the casting drum. However, such methods also have some drawbacks, such as complexity and throughput, as detailed below.

[0014] Therefore, there is a need for a less complicated and more cost-effective method for manufacturing thin, reinforced separators. [Prior art documents] [Patent documents]

[0015] [Patent Document 1] European Patent Application Publication No. 232923(A) [Patent Document 2] International Publication No. 2009 / 147084 Brochure [Patent Document 3] International Publication No. 2009 / 147086 Brochure Summary of the Invention

[0016] The present invention aims to provide a less complicated, cost-effective method for making thin, reinforced separators with sufficient mechanical quality and improved ionic conductivity.

[0017] This object is achieved by a method as claimed in claim 1.

[0018] Further objects of the present invention will become apparent from the following description. [Brief description of the drawings]

[0019] [Figure 1]FIG. 1 is a schematic diagram of a prior art method of making a reinforced separator using a supporting casting drum to coat a polymer solution on one side of a porous support. [Diagram 2] FIG. 2 is a schematic diagram of another prior art method of making a reinforced separator using a supporting casting belt to coat a polymer solution on one side of a porous support. [Diagram 3] FIG. 3 is a schematic diagram illustrating a method for making a reinforced separator according to the present invention using a supporting casting drum to coat one side of a porous support with a polymer solution. [Figure 4] FIG. 4 is a schematic diagram illustrating another method of making a reinforced separator according to the present invention using a supported engraved casting drum to coat a polymer solution on one side of a porous support. [Diagram 5] FIG. 5 is a schematic diagram showing two embodiments of the separator obtained by the method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Method for making reinforced separator The method for producing a reinforced separator is generally as follows: Providing a porous support; applying a dope solution comprising a polymer resin, hydrophilic particles, and a solvent to one side of a porous support; and performing a phase inversion of the applied dope solution.

[0021] The coated dope solution is typically impregnated into the porous support prior to the phase inversion step, or the porous support may be immersed in the coated dope immediately prior to carrying out the phase inversion.

[0022] The phase inversion process is generally carried out in a non-solvent for the polymer resin, and is also called Liquid Induced Phase Separation (LIPS).

[0023] FIG. 1 shows a prior art process for manufacturing a reinforced separator that coats a porous support on one side with a dope solution and uses a supporting casting drum.

[0024] A porous support (6) is provided on a casting drum (2). A dope solution is then applied (3) to the side of the porous support not in contact with the casting drum. The applied dope solution penetrates the porous support and, once the porous support is completely saturated with the dope solution, contacts the casting drum surface and, as the drum surface rotates, enters the coagulation bath (1). The coagulation bath contains a non-solvent for the polymer resin in the dope solution, typically water.

[0025] The applied dope solution comes into contact with the non-solvent of the coagulation bath (1) from only one side, so the resulting separator typically has small pores on the side in contact with the non-solvent and larger, less well defined pores on the opposite side of the separator, which is in contact with the casting drum, a so-called asymmetric separator.

[0026] The coagulated dope solution, also called a membrane, is at least partially embedded in a porous support, typically a fabric, which is then conducted to a washing section, a drying section (7), and finally wound up.

[0027] As the casting drum rotates out of the coagulation bath, its surface is wiped or scraped (8) and further dried in a drying zone (4) to present a completely dry surface onto which the porous support (6) is provided and onto which the dope solution is applied (3).

[0028] The degree of dope penetration into the porous support depends on the open area of ​​the support and the viscosity of the dope solution, but in most cases a high degree of penetration is achieved, which allows the dope solution to completely impregnate the porous support and contact the casting drum surface (2).

[0029] The separator (7) detaches from the casting drum surface only when the phase inversion (solidification) of the applied dope is complete. As long as the applied dope is not completely solidified, the separator remains attached to the casting drum.

[0030] Since only one side of the coating liquid is in contact with the non-solvent, the dope liquid in contact with the casting drum solidifies (solidifies), and the resulting separator can be detached from the casting drum. As long as solidification is not complete and the dope solution in contact with the casting drum remains liquid and molten, it is not possible to peel or remove the separator from the casting drum; any attempt to do so would result in tears in the applied dope layer.

[0031] The time required for complete solidification of the dope solution depends on the thickness of the applied dope layer, the composition of the dope solution, the type of non-solvent, the temperature of the coagulation bath, and other process parameters. When using a rotating casting drum, the time that the applied dope solution is in contact with the non-solvent of the coagulation bath is determined by the rotation speed of the drum. To allow complete solidification and release of the separator from the casting drum, the rotation speed, and therefore the production speed, is limited.

[0032] Increasing the diameter of the casting drum increases the contact time between the applied dope solution and the non-solvent in the coagulation bath, thereby increasing the production rate.

[0033] Another way to increase the production rate is to use an endless flat belt as shown in Figure 2. The flat belt (23) is typically made of stainless steel and runs over at least two rollers (21), one of which is driven. The use of a longer belt (23) increases the contact time between the dope solution (3) coated on the porous support (6) and the non-solvent in the coagulation bath (1), resulting in a faster production rate.

[0034] However, increasing the diameter of the casting drum or implementing a driven belt both make the manufacturing process more complicated and therefore more costly.

[0035] The above-mentioned problems are solved by the manufacturing method of the present invention, in which the casting drum is pre-wetted uniformly with a small amount of non-solvent. In this way, when the applied dope solution contacts the casting drum surface (after the porous support is completely impregnated), the presence of the non-solvent on the casting drum surface causes phase inversion (solidification) of the dope solution. The porous support is completely impregnated with the applied dope solution almost immediately after it is applied to the porous support. This method allows for a faster removal of the separator from the casting drum, without the need to increase the diameter of the drum or use a belt.

[0036] The method for producing a reinforced separator according to the present invention includes the steps of: i) providing a porous support (6) on a pre-wetted casting drum (23); ii) applying a dope solution (3) comprising a polymeric resin, hydrophilic inorganic particles, and a solvent to the porous support on a side other than the side that contacts the pre-wetted casting drum; iii) performing a phase inversion (9,1) of the applied polymer solution; iv) removing the reinforced separator (7) from the casting drum, The casting drum is pre-wetted with a non-solvent for the polymer resin.

[0037] The non-solvent referred to here may be a single solvent or a mixture of different solvents, as described below.

[0038] In one embodiment of the present invention, the casting drum is pre-wetted by applying a thin layer of a non-solvent to the surface of the casting drum.

[0039] The non-solvent can be used, for example, in dip coating, knife coating, extrusion coating, spray coating, etc. The coating may be applied to the casting drum by any suitable coating technique, such as spray coating, slide hopper coating, or the like.

[0040] The layer of non-solvent is applied over the surface area of ​​the casting drum of 1 m 2 Contains less than 50 g of non-solvent per unit.

[0041] The non-solvent used to pre-wet the casting drum is preferably the same non-solvent used in the liquid-induced phase inversion process (described below). In this case, the casting drum is preferably pre-wet by dip coating, with the coating (2) applied by application from a coagulation bath (1), as shown in Figure 3. An air knife or metering roll (5) may be used to control the layer thickness of the applied non-solvent.

[0042] If the layer of non-solvent on the casting drum is too thick, the porous support may become too wet with non-solvent, resulting in insufficient penetration of the applied dope solution into the porous support. Insufficient penetration of the dope solution into the porous support may result in the membrane (coagulated dope solution) peeling off from the porous support after the coagulation step. Sufficient penetration of the dope solution into the porous support ensures sufficient adhesion of the coagulated polymer layer to the porous support. Such good adhesion results in good mechanical properties of the separator and is important for the operation of the separator and its introduction into the electrolytic cell.

[0043] The viscosity of the non-solvent is generally much lower than that of the dope solution. If the layer of non-solvent on the casting drum is too thick, resulting in a porous fabric that is too wet with non-solvent, it may be difficult to coat the dope solution uniformly due to the so-called slip between the non-solvent and the dope solution. This is probably because the shear force built up by the viscous forces is insufficient to carry the entire mass of dope.

[0044] For these reasons, it is preferred that the thickness of the non-solvent layer on the casting drum is less than the thickness of the porous support, more preferably less than 50% and most preferably less than 20% of the thickness of the porous support.

[0045] In another embodiment of the present invention, a engraved roll is used as the casting drum, as shown in FIG.

[0046] An engraved roll or drum (23) rotates in the coagulation bath (1) causing the grid or engraving to fill with non-solvent. Excess non-solvent is preferably removed with a scraper or doctor blade (8).

[0047] The amount or volume of non-solvent liquid that is picked up by the engraved drum depends on the geometry and depth of the engraved cells in the drum.

[0048] The engraved pattern may consist of lines, dots, or a combination of both. A dot pattern is commonly referred to as a cell pattern.

[0049] The engraved cells may be square, pyramidal, hexagonal, or tri-helical, and may be interconnected by open channel engraving.

[0050] Cell count refers to the number of rows of cells per linear centimeter. Cell depth refers to the depth of the cells. Cell volume (cm 3 / m 2 ) refers to the amount of non-solvent that can be captured by the engraved roll and is determined by the number of cells and the cell depth.

[0051] The preferred cell volume is 25cm2 or 35cm3 depending on the engraving pattern, depth, and density of the lines or cells. 3 / m 2 Less than or even 10cm 3 / m 2 It may be less than.

[0052] For the square cell pattern, a cell count of 50 rows / cm and an engraving depth of 75 μm were used to create a 25 cm 3 / m 2 Using a cell count of 70 rows / cm and an engraving depth of 36 μm, a cell volume of 10 cm may be obtained. 3 / m 2 The cell volume may be obtained.

[0053] The pattern, for example lines or dots, may be engraved mechanically or with a laser.

[0054] FIG. 4 shows an enlarged view of the engraved casting drum (23), the porous support (6), and the resulting separator (7).

[0055] The porous support is made of fabric fibers (more on this later), depicted as circles in the enlarged portion of Figure 4. This shows the open area of ​​the porous support, which allows for good penetration of the dope solution into the porous support. The reinforced separator (7) consists of a porous support embedded in the solidified dope solution.

[0056] The advantage of using a sculptured casting drum is that the porous fabric (6) is immersed little or not at all in the pre-wet liquid (10), which allows for better penetration of the dope solution (3) into the fabric (6), resulting in better fixation or embedding of the fabric by the membrane.

[0057] Another advantage of using a pre-wet drum is that the drum quickly moves away from the not yet fully coagulated dope (7) with the fabric, allowing more solvent exchange to occur on both sides, which may increase production rates.

[0058] As described in more detail below, the phase inversion process may also include a Vapour Induced Phase Separation (VIPS) process (9 in FIG. 4).

[0059] If the surface tension of the non-solvent is too high to wet the drum surface well and evenly without dewetting spots, whether the drum is engraved or not, it may be necessary to add a surfactant to the pre-wet fluid to lower its surface tension.

[0060] The surface tension of the pre-wet liquid is preferably less than 40 mN / m.

[0061] A thickener may be added to the pre-wet liquid to increase its viscosity.

[0062] The viscosity of the pre-wet liquid is preferably less than 50 mPa·s.

[0063] The casting or engraving drum is preferably made of a wear-resistant material with a sufficiently high surface energy to allow good spreading of the doctored or "pre-wet" liquid. Materials that can be used for the drum surface include chrome plating, stainless steel, ceramic, etc.

[0064] The portion of the drum or engraved drum that is immersed in the coagulation bath is preferably about 30% to 70% of its circumference, more preferably about 40% to 60%.

[0065] Water electrolysis separator The separator for water electrolysis (FIG. 5) obtained by the production method according to the present invention includes a porous support 10 and a porous layer 20b. Such a separator including a porous support is often called a reinforced separator.

[0066] As detailed above, the preferred separator is prepared by applying a coating solution, commonly called a dope solution, containing a polymeric resin, hydrophilic inorganic particles, and a solvent to one side of a porous support, followed by a phase inversion process in which the polymeric resin forms a three-dimensional porous polymer network, resulting in a porous layer. When the dope solution is applied to the surface of the porous support, the dope solution penetrates into the support. After phase inversion, impregnation of the porous support ensures that the three-dimensional porous polymer network also permeates the porous support, which results in good adhesion between the porous hydrophilic layer and the porous support.

[0067] A preferred separator (100) is shown diagrammatically in Figure 5. The dope solution (20a) is applied to one side of the porous support (10), and then the support is preferably completely impregnated with the applied dope solution. After the phase inversion step (50), a separator (100) is obtained comprising the support (10) and a porous layer (20b).

[0068] The porous support is used to support and provide strength to the separator during the manufacturing process of the separator, i.e., the coating step and / or the solidification step described below. By reinforcing the separator with a temporary support during the manufacturing process, the separator can be easily washed, rewound, etc.

[0069] Additionally, the porous support provides strength and tear resistance to the separator during, for example, the conversion process in which the separator is cut into various formats, as well as the assembly process in which the separator is introduced between the electrodes of an alkaline electrolytic cell.

[0070] However, the porous support may adversely affect the ionic conductivity of the separator. After placement in the electrolytic cell of the alkaline electrolytic bath, reinforcement of the separator with a porous support is not necessarily required. In particular, in the so-called zero-gap configuration described below, the separator does not vibrate when bubbles escape, and therefore the separator does not experience fatigue that could lead to cracks or breakage.

[0071] According to another embodiment of the invention, the porous support can be substantially removed from the separator, preferably by an alkaline solution, more preferably by the electrolyte of an alkaline electrolytic cell, as disclosed in unpublished European Patent Application No. 20183861.2(A) filed on March 7, 2020 by Agfa Gevaert.

[0072] The alkaline solution or electrolyte of the alkaline electrolytic cell is preferably a 10% to 40% by weight KOH aqueous solution, more preferably a 20% to 35% by weight KOH aqueous solution. A particularly preferred alkaline solution or electrolyte is a 30% by weight KOH aqueous solution.

[0073] The temperature of the alkaline solution or electrolyte is preferably 50°C or higher, more preferably 80°C or higher.

[0074] The porous support is preferably removed by dissolving or decomposing the support with an alkaline solution or electrolyte used in the electrolytic cell.

[0075] As mentioned above, the presence of a porous support that reinforces the separator may adversely affect the ionic conductivity of the separator. It is preferable that the ionic conductivity of the separator is improved after removing the temporary support.

[0076] As shown diagrammatically in Figure 5, the porous support may optionally be removed prior to incorporation into the electrolytic cell stack by treating the separator (100) with an alkaline solution (60), thereby obtaining the separator (200). With reference to Figures 3 and 4, such alkaline treatment is preferably carried out by conducting the separator (7) from the coagulation bath (1) into an alkaline bath.

[0077] The thickness of the separator is preferably between 50 μm and 500 μm, more preferably between 100 μm and 350 μm.

[0078] The pore size of the separator must be small enough to avoid gas crossover and prevent recombination of hydrogen and oxygen, while larger pore sizes are preferred to ensure efficient transport of hydroxyl ions from the cathode to the anode. To efficiently transport hydroxyl ions, the electrolyte must be able to penetrate the separator efficiently.

[0079] The maximum pore diameter (PDmax) of the separator is preferably between 0.05 μm and 2 μm, more preferably between 0.10 μm and 1 μm, and most preferably between 0.15 μm and 0.5 μm.

[0080] The pore size referred to here is preferably measured using the bubble point test method described in Method F316 of the American Society for Testing and Materials (ASMT).

[0081] The porosity of the separator is preferably between 30% and 70%, more preferably between 40% and 60%. A separator having a porosity within the above range generally has excellent ion permeability and excellent gas barrier properties, since the pores of the diaphragm are continuously filled with the electrolyte.

[0082] Dope solution application The dope solution (3) can be coated or cast onto one side of the porous support (6) using any known coating system, preferably using a coating system selected from the group consisting of bar or rod coating, extrusion coating, and slot coating.

[0083] In a highly preferred embodiment, the dope solution is applied by slot die coating. When the dope solution is applied to one side of the support, one slot coating die is generally used. The slot die head can keep the dope solution at a certain temperature, distribute the dope solution evenly on the porous support, and adjust the flow rate to control the film thickness of the applied dope solution.

[0084] When used for slot die coating, the viscosity of the dope solution depends on the coating temperature and 1s -1 At a shear rate of 1 Pa·s to 500 Pa·s, the viscosity is preferably between 10 Pa·s and 100 Pa·s.

[0085] The dope solution is preferably shear thinning. Shear rate 100 s -1 Viscosity at shear rate 1s -1 is preferably at least 2, more preferably at least 2.5, and most preferably at least 5.

[0086] The porous support (6) is preferably a continuous web.

[0087] Immediately after application, the porous support is preferably in a state where it is impregnated with the dope solution, and preferably the support is in a state where it is completely impregnated with the applied dope solution.

[0088] Phase inversion process After the dope solution is coated on the support, the coated dope solution is subjected to a phase inversion process, in which the coated dope solution is converted into a porous hydrophilic layer.

[0089] Any phase inversion mechanism may be used to create a porous hydrophilic layer from the coated dope solution.

[0090] The phase inversion process preferably comprises a so-called liquid induced phase separation (LIPS) process, a vapor induced phase separation (VIPS) process, or a combination of a VIPS process and a LIPS process. The phase inversion process preferably comprises both a VIPS process and a LIPS process.

[0091] Both LIPS and VIPS are non-solvent induced phase inversion processes.

[0092] In the LIPS process, the support coated with the dope solution is contacted with a non-solvent for the polymer resin of the dope solution that is miscible with the solvent of the dope solution.

[0093] This is typically accomplished by immersing the support coated with the dope solution in a non-solvent bath, also called a coagulation bath (1).

[0094] Preferred non-solvents include water; a mixture of water and an aprotic solvent selected from the group consisting of N-methylpyrrolidone (NMP), dimethylformamide (DMF), dimethylsulfoxide (DMSO), and dimethylacetamide (DMAC); an aqueous solution of a water-soluble polymer such as PVP or PVA; or a mixture of water and an alcohol such as ethanol, propanol, isopropanol, etc.

[0095] The most preferred non-solvent is water.

[0096] The temperature of the coagulation bath is preferably between 20°C and 90°C, more preferably between 40°C and 70°C.

[0097] The migration of the solvent from the coated polymer layer to the non-solvent bath and back to the polymer layer causes phase inversion and the formation of a three-dimensional porous polymer network. The coated dope solution impregnates the support, resulting in good adhesion between the resulting hydrophilic layer and the support.

[0098] In the VIPS process, a substrate coated with a dope solution is exposed to vapors of a non-solvent, preferably humid air.

[0099] The coagulation step preferably includes both a VIPS step and a LIPS step. Preferably, the support coated with the dope solution is first exposed to moist air (VIPS step) before being immersed in a coagulation bath (LIPS step).

[0100] In the manufacturing method shown in Figures 3 and 4, VIPS is carried out in region 9, which is between the slot coating die (3) and the non-solvent surface (20) in the coagulation bath (1) and is shielded from the environment by, for example, an insulating metal plate (15).

[0101] The degree and rate of water movement in the VIPS process can be controlled by adjusting the air velocity, the relative humidity and temperature of the air, and the exposure time.

[0102] The exposure time may be adjusted by varying the distance between the slot coating die (3) and the non-solvent surface (20) in the coagulation bath (1) and / or the speed at which the elongated web 6 is conveyed from the slot coating die towards the coagulation bath.

[0103] The relative humidity of the VIPS region (9) may be controlled by the temperature of the coagulation bath and by shielding the VIPS region (15) from the environment and the coagulation bath.

[0104] The air velocity may be regulated by the rotational speed of a ventilator integrated within the VIPS area (9).

[0105] After the phase inversion step, preferably after the LIPS step carried out in a coagulation bath, a washing step may be carried out.

[0106] After the phase inversion step or after the optional washing step, a drying step may be performed.

[0107] Removal of temporary support In embodiments in which a temporary support is used, the temporary support may be removed before or after the separator is placed between the electrodes of the electrolytic cell, as described below.

[0108] If the temporary support is removed before placing the separator in the alkaline electrolytic cell, any materials dissolved from the porous support by the electrolyte of the alkaline electrolytic cell after removal of the support, or decomposition products of the porous support, will not adversely affect the electrocatalytic properties of the electrodes or the electrolysis process, however, removing the support outside the electrolytic cell provides no advantage of extra reinforcement for manipulation or handling of the separator sheets when assembling the electrolytic cell stack.

[0109] To remove the temporary support, it is preferable to expose the separator to an alkaline solution after the phase inversion step.

[0110] The separator with the porous support is preferably placed in a bath containing an alkaline solution.

[0111] After the alkaline treatment to remove the support, the resulting separator is preferably subjected to a washing step, optionally followed by a drying step.

[0112] The alkaline solution is preferably a 20% to 40% by weight aqueous KOH solution, and more preferably a 30% by weight aqueous KOH solution.

[0113] The temperature of the alkaline solution is preferably 50° C. or higher.

[0114] porous support The porous support is generally used to reinforce the separator and ensure its mechanical strength.

[0115] The thickness of the support is preferably from 20 to 400 μm, more preferably from 40 to 200 μm, and most preferably from 60 to 100 μm.

[0116] The porous support is selected from the group consisting of a porous cloth, a porous metal plate, and a porous ceramic plate. You can choose.

[0117] The porous support is preferably a porous fabric, more preferably a porous polymeric fabric.

[0118] The porous polymer fabric may be woven or nonwoven. Woven fabrics generally have better dimensional stability and uniformity of open area and thickness. However, woven fabrics with a thickness of 100 μm or less are more complicated to manufacture and more expensive. Nonwoven fabrics are less complicated to manufacture, even if they are 100 μm or less in thickness. In addition, nonwoven fabrics may have a larger open area.

[0119] The open area of ​​the porous support is preferably between 30% and 80%, more preferably between 40% and 70%, to ensure good penetration of the electrolyte into the support.

[0120] Suitable porous polymer fabrics include fabrics made of polypropylene, polyethylene (PE), polysulfone (PS), polyphenylene sulfide (PPS), polyamide / nylon (PA), polyethersulfone (PES), polyphenylsulfone (PPSU), polyethylene terephthalate (PET), polyetheretherketone (PEEK), sulfonated polyetheretherketone (s-PEEK), monochlorotrifluoroethylene (CTFE), copolymers of ethylene and tetrafluorethylene (ETFE) or chlorotrifluorethylene (ECTFE), polyimide, polyetherimide, and m-aramid.

[0121] Preferred polymer fabrics are those made of polypropylene (PP) or polyphenylene sulfide (PPS), most preferably those made of polyphenylene sulfide (PPS).

[0122] Polyphenylene sulfide-based porous supports have high resistance to high-temperature, high-concentration alkaline solutions and high chemical stability against active oxygen generated from the anode during the water electrolysis process. Polyphenylene sulfide can also be easily processed into various forms, such as woven or nonwoven fabrics.

[0123] The density of the porous support is 0.1 g / cm 3 from 0.7 g / cm 3 It is preferable that the ratio is between 1 and 2.

[0124] Preferably the porous support is a continuous web to allow manufacturing processes such as those disclosed in EP 1 776 490(A) and WO 2009 / 147084.

[0125] The width of the web is preferably between 30 cm and 300 cm, more preferably between 40 cm and 200 cm.

[0126] In another embodiment of the present invention, the porous support may be a so-called temporary porous support, as described above.

[0127] Such a temporary support does not need to be resistant to a highly alkaline electrolyte, since it is removed in the electrolytic cell.

[0128] To design a fabric that can be removed from the separator by alkaline treatment, the following approach was taken: Chi is preferred: Introducing alkali-solubilizing groups into the main polymer of the textile fiber; Introducing alkaline reactive groups into the base polymer of the textile fiber; and Introducing an alkali-decomposable functional group into the backbone of the main polymer of the fabric fiber.

[0129] Preferred alkali-solubilizing groups are functional groups having a pKa of 10 or less, more preferably 8 or less, and most preferably 6 or less. Particularly preferred alkali-solubilizing groups are selected from the group consisting of phenols, sulfonamides, carboxylic acids, phosphonic acids, phosphate esters, and sulfonic acids, with carboxylic acids being particularly preferred.

[0130] Preferred alkaline-reactive groups are selected from the group consisting of esters and anhydrides, with esters being especially preferred.

[0131] Preferred alkali-decomposable groups are esters.

[0132] The textile fibers may be selected from natural polymers, synthetic polymers, or combinations thereof.Preferably, the textile is selected from the group consisting of cotton, silk, linen, jute, hemp, modal, bamboo, pineapple, basalt, ramie, polyester, acrylic, glass fiber, aramid fiber, polyamide, polyolefin, polyurethane, and mixtures thereof.

[0133] Several strategies have been disclosed for designing alkali-soluble fabrics.

[0134] Alkali-solubilization of cotton by post modification is a long-known technique used to engineer alkali-soluble cellulosic fabrics, as disclosed in American Dyestuff Reporter, 50(19), 67-74 (1961) and U.S. Patent No. 3,087,775 (U.S. Department of Agriculture). Low-functionalized carboxymethylcellulose-type polymers are particularly preferred.

[0135] The polyamide backbone can be functionalized with alkali decomposable functional groups such as certain esters as disclosed in US Pat. No. 5,457,144 (Rohm and Haas Company) to design alkali soluble polyamides.

[0136] The polyolefins can be functionalized or copolymerized with monomers containing alkali-reactive or alkali-soluble groups, preferably selected from the group consisting of anhydrides and carboxylic acids. Copolymers of ethylene with acrylic or methacrylic acid and polyethylene graft-functionalized with maleic anhydride are particularly preferred functionalized polyolefins.

[0137] In the most preferred embodiment, the fabric is polyester-based, since the fabric itself is inherently alkaline degradable. Particularly preferred polyesters are selected from the group consisting of polyethylene terephthalate, polylactic acid, polycaprolactone, and copolymers thereof. Polylactic acid is particularly preferred due to its biodegradability and the fact that it is produced from renewable resources.

[0138] A strategy to design polyesters with enhanced alkali solubility and degradability is based on the introduction of hydrophilic blocks, preferably polyethylene glycol fragments, into the polyester structure, as disclosed in Japanese Patent No. 7145509 (Toyobo), and Chinese Patent No. 1439751 (Jinan Zhenghao Advanced Fiber Co.) and Korean Patent No. 2018110827 (Toray Chemical Co.). Strategies have been disclosed that are optionally combined with the introduction of additional water-solubilizing groups, such as those disclosed in US Pat. No. 6,393,992, issued to Cal Korea Inc. Yet another strategy can be based on the introduction of reactive esters in the polyester backbone, such as oxalic acid esters, thereby improving the susceptibility of the fibers to alkaline treatment.

[0139] The polymer fabric may be used alone or two or more polymer fabrics may be used in combination to make the support.

[0140] After the support is removed by the electrolyte of the alkaline electrolytic cell, materials dissolved from the support or decomposition products of the support preferably do not adversely affect the electrocatalytic properties of the electrode or the electrolytic process.

[0141] Preferably, at least 50%, more preferably at least 75%, most preferably at least 90%, particularly preferably at least 95% of the support is removed by the alkaline solution or electrolyte of the alkaline electrolytic cell. In a most preferred embodiment, the support is completely removed by the electrolyte of the alkaline electrolytic cell.

[0142] The support is preferably substantially removed after being left in the alkaline solution or electrolyte of the alkaline electrolytic cell for 24 to 48 hours, however, the support may also be substantially removed after being left in the alkaline solution or electrolyte of the alkaline electrolytic cell for 2 weeks or 1 month.

[0143] However, the temporary support must be resistant to various components, particularly solvents, used in the method for producing the separator.

[0144] For example, in order to enable a coating process in which a dope solution is applied onto the temporary support, the temporary support must be resistant to the solvent of the dope solution used in the method for producing a separator described below, for preferably at least 0.5 minutes, more preferably at least 1 minute, most preferably at least 2 minutes, and particularly preferably at least 5 minutes.

[0145] After the coagulation step described below, the solvent of the dope solution is removed, leaving a very low residual amount (preferably 10 g / m) that does not affect the support. 2 less than 5 g / m 2 (less than)

[0146] Polymer Resin The porous layer comprises a polymeric resin.

[0147] The polymer resin forms a three-dimensional porous network as a result of a phase inversion process in the fabrication of the separator, as described below.

[0148] The polymer resin may be selected from fluororesins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), olefin resins such as polypropylene (PP), and aromatic hydrocarbon resins such as polyethylene terephthalate (PET) and polystyrene (PS). The polymer resin may be used alone or in combination of two or more kinds of polymer resins.

[0149] PVDF and vinylidene fluoride (VDF) copolymers are preferred from the viewpoints of oxidation / reduction resistance and film-forming properties. Among these, VDF, hexanefluoropropylene (HFP), and chlorotrifluoroethylene (CTFE) trimers are preferred because of their excellent swelling properties, heat resistance, and adhesion to electrodes.

[0150] Another preferred polymer resin is an aromatic hydrocarbon resin, which has excellent heat resistance and alkali resistance. Examples of the aromatic hydrocarbon resin include polyethylene terephthalate, polybutylene terephthalate, polybutylene naphthalate, polystyrene, polysulfone, polyethersulfone, polyphenylene sulfide, polyphenylsulfone, polyacrylate, polyetherimide, polyimide, and polyamideimide.

[0151] Particularly preferred polymer resins are selected from the group consisting of polysulfone, polyethersulfone, and polyphenylsulfone, with polysulfone being most preferred.

[0152] The molecular weight (Mw) of polysulfone, polyethersulfone, and polyphenylsulfone is preferably between 10,000 and 500,000, more preferably between 25,000 and 250,000. If Mw is too low, the physical strength of the porous layer may be insufficient. If Mw is too high, the viscosity of the dope solution may be too high.

[0153] Examples of polysulfones, polyethersulfones, and combinations thereof are disclosed in EP 3085815(A), paragraphs 0021-0032.

[0154] The polymer resin may be used alone or in combination of two or more kinds of polymer resins.

[0155] inorganic hydrophilic particles The hydrophilic layer also contains hydrophilic particles.

[0156] Preferred hydrophilic particles are selected from metal oxides and metal hydroxides.

[0157] Preferred metal oxides are selected from the group consisting of zirconium oxide, titanium oxide, bismuth oxide, cerium oxide, and magnesium oxide.

[0158] Preferred metal hydroxides are selected from the group consisting of zirconium hydroxide, titanium hydroxide, bismuth hydroxide, cerium hydroxide and magnesium hydroxide. Particularly preferred magnesium hydroxides are disclosed in EP 3 660 188 A, paragraphs 0040 to 0063.

[0159] Another preferred hydrophilic particle is barium sulfate particle.

[0160] Other hydrophilic particles that may be used include nitrides and carbides of Group IV elements of the periodic table.

[0161] The hydrophilic particles preferably have a D50 particle size of 0.05 μm to 2.0 μm, more preferably 0.1 μm to 1.5 μm, most preferably 0.15 μm to 1.00 μm, and especially preferably 0.2 μm to 0.75 μm. The D50 particle size is preferably 0.7 μm or less, preferably 0.55 μm or less, and more preferably 0.40 μm or less.

[0162] D50 particle size is also known as the median size or midpoint of a particle size distribution. It is the particle size value at 50% of the cumulative distribution. For example, if D50=0.1um, then 50% of the particles are larger than 1.0um and 50% are smaller than 1.0um.

[0163] The D50 particle size can be determined, for example, by using the Master It is preferred to carry out the measurement using laser diffraction with a rsizer.

[0164] The amount of hydrophilic particles relative to the total dry weight of the porous layer is preferably at least 50% by weight, more preferably at least 75% by weight.

[0165] Preferably, the weight ratio of hydrophilic particles to polymeric resin is greater than 60 / 40, more preferably greater than 70 / 30, and most preferably greater than 75 / 25.

[0166] Dope Solution The dope solution preferably includes a polymer resin as described above, hydrophilic particles as described above, and a solvent.

[0167] The solvent of the dope solution is preferably an organic solvent in which the polymer resin can be dissolved, and further, the organic solvent is preferably miscible with water.

[0168] The solvent is preferably selected from N-methyl-pyrrolidone (NMP), N-ethyl-pyrrolidone (NEP), N-butyl-pyrrolidone (NBP), N,N-dimethylformamide (DMF), formamide, dimethylsulfoxide (DMSO), N,N-dimethylacetamide (DMAC), acetonitrile, and mixtures thereof.

[0169] A highly preferred solvent is NBP, especially for health and safety reasons.

[0170] The dope solution may further contain other ingredients to optimize the properties of the resulting polymer layer, such as its porosity and maximum pore size at the outer surface.

[0171] The dope solution preferably contains additives to optimize the surface and internal pore size of the porous layer. Such additives may be organic compounds, inorganic compounds, or a combination thereof.

[0172] Organic compounds that can affect the pore formation of the porous layer include polyethylene glycol, polyethylene oxide, polypropylene glycol, ethylene glycol, tripropylene glycol, glycerol, polyhydric alcohols, dibutyl phthalate (DBP), diethyl phthalate (DEP), diundecyl phthalate (DUP), isononanoic acid or neodecanoic acid, polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl acetate, polyethyleneimine, polyacrylic acid, methylcellulose, and dextran.

[0173] Preferred organic compounds capable of influencing the pore formation of the porous layer are selected from polyethylene glycol, polyethylene oxide, polyvinylpyrrolidone.

[0174] Preferred polyethylene glycol has a molecular weight of 10,000 to 50,000, preferred polyethylene oxide has a molecular weight of 50,000 to 300,000, and preferred polyvinylpyrrolidone has a molecular weight of 30,000 to 1,000,000.

[0175] A particularly preferred organic compound capable of influencing the pore formation of the porous layer is glycerol.

[0176] The amount of the compound capable of influencing pore formation is preferably between 0.1% and 15% by weight, more preferably between 0.5% and 5% by weight, relative to the total weight of the dope solution.

[0177] Inorganic compounds that can affect pore formation include calcium chloride, magnesium chloride, lithium chloride, and barium sulfate.

[0178] Two or more types of additives that affect pore formation may be used in combination.

[0179] When two polymer layers are coated onto a porous support, the dope solutions used for both layers may be the same or different from each other.

[0180] electrolytic cell The separator for alkaline water electrolysis according to the present invention can be used in an alkaline water electrolysis cell. An electrolytic cell typically consists of two electrodes, an anode and a cathode, separated by a separator, between which resides an electrolyte.

[0181] When electrical energy (voltage) is supplied to the electrolysis cell, hydroxyl ions in the electrolyte are oxidized to oxygen at the anode, and water is reduced to hydrogen at the cathode. The hydroxyl ions produced at the cathode travel through the separator to the anode. The separator prevents the hydrogen gas and oxygen gas produced during electrolysis from mixing.

[0182] The electrolyte is generally an alkaline solution. A preferred electrolyte is an aqueous solution of an electrolyte selected from sodium hydroxide or potassium hydroxide. Potassium hydroxide electrolyte is often preferred due to its high specific conductivity. The concentration of the electrolyte in the electrolyte is preferably 10% to 40% by weight, more preferably 20% to 35% by weight, based on the total weight of the electrolyte. A highly preferred electrolyte is a 30% by weight aqueous solution of KOH. The temperature of the electrolyte is preferably 50°C to 120°C, more preferably 80°C to 100°C.

[0183] The electrodes generally comprise a substrate provided with a so-called catalytic layer, which may be different for the anode, where oxygen is produced, and for the cathode, where hydrogen is produced.

[0184] Typical substrates are made of conductive materials selected from the group consisting of nickel, iron, mild steel, stainless steel, vanadium, molybdenum, copper, silver, manganese, platinum group elements, graphite, and chromium. The substrate may also be made of a conductive alloy of two or more metals, or a mixture of two or more conductive materials. The preferred material is nickel or a nickel-based alloy. Nickel has good stability in strong alkaline solutions, good electrical conductivity, and is relatively inexpensive.

[0185] The catalytic layer provided on the anode preferably has a high oxygen generating ability. The catalytic layer preferably contains nickel, cobalt, iron, and a platinum group element. The catalytic layer may contain these elements as elemental metals, compounds (e.g., oxides), composite oxides or alloys of multiple metal elements, or mixtures thereof. Preferred catalytic layers include plated nickel, plated alloys of nickel and cobalt or nickel and iron, composite oxides containing nickel and cobalt such as LaNiO3, LaCoO3, and NiCo2O4, compounds of platinum group elements such as iridium oxide, or carbon materials such as graphene.

[0186] Raney nickel structures are formed by selectively leaching aluminum or zinc from Ni-Al or Ni-Zn alloys. The lattice vacancies formed during leaching provide a large surface area and a high density of lattice defects, which act as active sites for electrocatalytic reactions.

[0187] The catalyst layer may further contain organic materials such as polymers to improve durability and adhesion to the substrate.

[0188] The catalytic layer provided on the cathode preferably has a high hydrogen generating capacity. The catalytic layer preferably contains nickel, cobalt, iron, and a platinum group element. To achieve the desired activity and durability, the catalytic layer may contain a compound such as a metal or an oxide, a composite oxide or alloy of a plurality of metal elements, or a mixture thereof. Preferred catalytic layers are formed of Raney nickel; a Raney alloy consisting of a combination of a plurality of materials (e.g., nickel and aluminum, nickel and tin); a porous coating made by spraying a nickel compound or a cobalt compound by plasma spraying; an alloy or composite compound of nickel and an element selected from, for example, cobalt, iron, molybdenum, silver, and copper; elemental metals and oxides of platinum group elements (e.g., platinum and ruthenium) having high hydrogen generating capacity; a mixture of elemental metals or oxides of these platinum group elements and compounds of other platinum group elements (e.g., iridium or palladium) or compounds of rare earth metals (e.g., lanthanum and cerium); and a carbon material (e.g., graphene).

[0189] To provide greater catalytic activity and durability, the above-mentioned materials may be laminated as multiple layers or may be contained in the catalyst layer.

[0190] Organic materials, such as polymeric materials, may be included to improve durability or adhesion to the substrate.

[0191] In so-called zero-gap electrolysis cells, the electrodes are in direct contact with the separator, thereby reducing the space between the electrodes. Mesh-type or porous electrodes are used to allow electrolyte filling of the separator and to efficiently remove the oxygen and hydrogen gas produced. Such zero-gap electrolysis cells have been shown to operate at higher current densities.

[0192] A typical alkaline water electrolyser, as previously mentioned, comprises a number of electrolysis cells, also referred to as a stack of electrolysis cells.

Claims

1. providing a porous support (6) on a pre-wetted casting drum (23); applying a dope solution (3) comprising a polymeric resin and hydrophilic inorganic particles to the porous support on a side other than the side that contacts the pre-wetted casting drum; carrying out a phase inversion (9,1) of the applied dope solution, thereby obtaining a reinforced separator; and removing the reinforcing separator (7) from the casting drum, the casting drum is pre-wetted with a non-solvent for the polymer resin; the phase inversion step comprises a liquid induced phase separation (LIPS) step using a non-solvent for the polymer resin of the dope solution, and the phase inversion step further comprises a vapor induced phase separation (VIPS) step; How to make a reinforced separator.

2. The method of claim 1 , wherein the pre-wet casting drum is obtained by applying a layer of a non-solvent to the casting drum.

3. 10. The method of claim 1, wherein a engraved casting drum is used.

4. The pre-wetted casting drum has a surface area of ​​1 m 2 13. The method of claim 1, comprising less than 50 g of non-solvent per unit area.

5. 2. The method of claim 1, wherein the non-solvent has a surface tension of less than 40 mN / m.

6. The method of claim 1 , wherein the non-solvent comprises a surfactant.

7. The method of claim 1 , wherein the non-solvent comprises a thickening agent.

8. 10. The method of claim 1, wherein the non-solvent for pre-wetting the casting drum and the non-solvent for the LIPS process are the same.

9. The method of claim 1 , wherein the polymer resin is selected from the group consisting of polysulfone, polyethersulfone, and polyphenylsulfide.

10. 2. The method of claim 1, wherein the hydrophilic inorganic particles are selected from the group consisting of zirconium oxide particles, zirconium hydroxide particles, magnesium oxide particles, magnesium hydroxide particles, titanium oxide particles, titanium hydroxide particles, and barium sulfate particles.

11. The method of claim 1, wherein the porous support has an open area of ​​from 30% to 80%.

12. The method of claim 1 , wherein the porous support has a thickness of from 40 μm to 200 μm.

13. The method of claim 1 , wherein the reinforced separator has a thickness of from 100 μm to 350 μm.

Citation Information

Patent Citations

  • Improved ion-permeable diaphragms for electrolytic cells

    EP0232923A1

  • Asymmetric supported membranes for direct osmotic concentration

    JP2000506439A

  • Method of manufacturing coating film and method of manufacturing separator for non-aqueous secondary battery

    JP2010149011A

  • Inorganic-organic composite membrane, and diaphram for electrochemical element

    JP2020007574A

  • Process for producing an ion-permeable web-reinforced separator

    WO2009147084A1